Manipulation of the Alternative NF‐κB Pathway in Mice Has Sexually Dimorphic Effects on Bone. (23rd August 2018) - Zarei, Allahdad; Yang, Chang; Gibbs, Jesse; Davis, Jennifer L; Ballard, Anna; Zeng, Rong; Cox, Linda; Veis, Deborah J
ABSTRACT: Alternative NF‐κB signaling promotes osteoclastogenesis and pathological bone loss, but the effect of sex on phenotype has not been explored. We disrupted alternative NF‐κB signaling by deletion of upstream kinase NF‐κB‐inducing kinase (NIK) or NF‐κB subunit RelB and found that both NIK‐deficient and RelB‐deficient female mice possessed more than twofold higher trabecular bone mass compared to controls, whereas no differences were observed in males. In vitro, RelB‐deficient precursors from female mice showed a more severe osteoclast (OC) differentiation defect than male, while WT had no sex bias. Next, we asked whether pharmacologic activation of alternative NF‐κB by inhibitor of apoptosis (IAP) antagonist BV6 has sex‐dependent effects on bone. Unlike male mice that lost bone, female mice on BV6 for 4 weeks showed no changes in either trabecular bone mass or OC number. Because estrogen generally suppresses NF‐κB, we hypothesized that estrogen protects bone from BV6 effects in vivo. Thus, we performed ovariectomy or sham surgery in female mice, then treated with BV6 or vehicle for 4 weeks. Although ovariectomy caused bone loss, BV6 did not have any additional impact, suggesting that direct estrogen effects do not cause resistance to BV6 in vivo. The osteopenic effects of IAP antagonists in males may have implications for their use in cancer therapy. © 2018 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.